Comparative analyses of chloroplast genomes from 22 Lythraceae species: inferences for phylogenetic relationships and genome evolution within Myrtales - Gu, Cuihua; Ma, Li; Wu, Zhiqiang; Chen, Kai; Wang, Yixiang (BMC plant biology, 2019)
Background Lythraceae belongs to the order Myrtales, which is part of Archichlamydeae. The family has 31 genera containing approximately 620 species of herbs, shrubs and trees. Of these 31 genera, five large genera each possess 35 or more species. They are Lythrum , with 35; Rotala , with 45; Nesaea , with 50; Lagerstroemia , with 56; and Cuphea , with 275 species. Results We reported six newly sequenced chloroplast (cp) genomes ( Duabanga grandiflora , Trapa natans , Lythrum salicaria , Lawsonia inermis , Woodfordia fruticosa and Rotala rotundifolia ) and compared them with 16 other cp genomes of Lythraceae species. The cp genomes of the 22 Lythraceae species ranged in length from 152,049 bp to 160,769 bp. In each Lythraceae species, the cp genome contained 112 genes consisting of 78 protein coding genes, four ribosomal RNAs and 30 transfer RNAs. Furthermore, we detected 211–332 simple sequence repeats (SSRs) in six categories and 7–27 long repeats in four categories. We selected ten divergent hotspots ( ndhF, matK, ycf1, rpl22, rpl32, trnK-rps16, trnR-atpA, rpl32-trnL, trnH-psbA and trnG-trnR ) among the 22 Lythraceae species to be potential molecular markers. We constructed phylogenetic trees from 42 Myrtales plants with 8 Geraniales plants as out groups. The relationships among the Myrtales species were effectively distinguished by maximum likelihood (ML), maximum parsimony (MP) and Bayesian inference (BI) trees constructed using 66 protein coding genes. Generally, the 22 Lythraceae species gathered into one clade, which was resolved as sister to the three Onagraceae species. Compared with Melastomataceae and Myrtaceae, Lythraceae and Onagraceae differentiated later within Myrtales. Conclusions The study provided ten potential molecular markers as candidate DNA barcodes and contributed cp genome resources within Myrtales for further study.